Quality of Public Service at Bara Permai Health Center, Palopo City - Syah, Syahiruddin; Rhamadan, Aldian; Kamal, Kasmad (Universitas Negeri Makassar, 2022)
The purpose of this study was to determine the quality of public services at the Bara Permai Health Center, Palopo City. To achieve this goal, qualitative methods are used with descriptive data elaboration. A data collection technique is carried out by observation, interviews and documentation using qualitative descriptive analysis techniques. The results of the research show that in terms of (1) Tangible Dimensions, the assessment of the quality of public services at the Bara Health Center in the tangible dimension shows that the quality of service is still low. This is caused by the inconvenience of the service place. The discomfort is caused by a fan that is still lacking. (2) Dimension of Reliability, the results of quality measurements carried out on the dimension of reliability show that the quality of service is good. This is due to the skill of employees in using service tools such as using computers. (3) Dimensions of Responsiveness, the assessment of service quality at the Bara Permai Health Center in the dimension of responsiveness shows that the officers in providing services have responded to all service users. The officers have also provided fast, precise, and careful service. (4) Dimension of Assurance, the assessment of service quality at Bara Permai Health Center in the dimension of assurance shows that officers in providing services have provided guarantees on time, cost and legality in services. (5) Dimensions of Empathy the assessment of service quality at the Bara Permai Health Center, the dimensions of empathy indicate that the quality of service is good. This is due to the friendliness of employees in serving the community, namely the empathetic attitude of service officers shown by giving smiles, greetings and greetings to the community when doing services.